Haemodynamic changes after delivery room surfactant administration to very low birth weight infants. Issue 5 (10th June 2010) - Sehgal, Arvind; Mak, Wendy; Dunn, Michael; Kelly, Edmond; Whyte, Hilary; McCrindle, B; McNamara, Patrick J
Abstract : Introduction: Surfactant replacement therapy (SRT) reduces respiratory morbidity and mortality in premature infants. The goal of this study was to characterise the effects of delivery room SRT on the ductus arteriosus and early neonatal haemodynamics. Methods: A prospective observational study was conducted in preterm infants of less than 32 weeks' gestation who received SRT within 30 min of birth. Serial echocardiography was performed before and after SRT. Characteristics of the ductus arteriosus, myocardial performance, right ventricular output (RVO) and left ventricular output (LVO) and the ratio of RVO:LVO were measured. Results: Sixteen babies, born at 28.3±1.3 weeks' gestation and weighing 1289±224 g, were studied. SRT was associated with an improvement in the arterial oxygen tension:fractional inspired oxygen ratio (p<0.001), increased systolic and decreased diastolic arterial pressure (p<0.05). The ductus arteriosus was patent in all and transductal flow was unrestrictive and exclusively left-to-right after SRT. An increase in transductal diameter (p<0.001), left atrium:aortic ratio (p=0.006) but a decrease in left ventricular end-diastolic dimension (p=0.02) was identified. Conclusion: SRT administration was followed by increased RVO but decreased LVO, resulting in an increased RVO:LVO ratio and an increase in ductal size. Delivery room administration of SRT is associated with major haemodynamic changes. The impact of these changes needs prospective evaluation.